Almanac of World War I - Burg, David F. (University Press of Kentucky, 2010)
"Provides a day-by-day account of the action on all fronts and of the events surrounding the conflict, from the guns of August 1914 to the November 1918 Armistice and its troubled aftermath. Daily entries, topical descriptions, biographical sketches, maps, and illustrations combine to give a ready and succinct account of what was happening in each of the principal theaters of war